2012
DOI: 10.1242/jeb.076760
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced erythropoiesis in mice exposed to low environmental temperature

Abstract: SUMMARYHematopoietic responses to environmental factors are not fully characterized. Polycythemia has been reported during exposure to low temperatures in ectothermic animals. The relationship between the causes of polycythemia and erythropoiesis during low temperature exposure is not fully understood. In this study, we exposed C57BL/6 mice to 5°C and monitored the blood cell counts and erythropoiesis. The hematocrit level increased from 45.6 to 52.2% after 14days. Likewise, the hemoglobin concentration, init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…Early erythroid cells were diminished in the spleen and bone marrow on days 2 or 4 and 5, respectively, but the numbers quickly expanded by day 7. Additionally, erythropoiesis appeared to function normally in the spleen and bone marrow of these animals, as expected [22].…”
Section: Discussionsupporting
confidence: 78%
“…Early erythroid cells were diminished in the spleen and bone marrow on days 2 or 4 and 5, respectively, but the numbers quickly expanded by day 7. Additionally, erythropoiesis appeared to function normally in the spleen and bone marrow of these animals, as expected [22].…”
Section: Discussionsupporting
confidence: 78%
“…Accumulating evidences have shown that erythropoiesis responds to environmental stresses such as hypoxia and low temperature 32 33 34 35 . Cell metabolism alters significantly and produces very different metabolic produces, such as lactic acid, when HSCs adopt to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Maekawa et al 2013 observed erythrocyte counts enhanced by low temperature to increase oxygen supply to peripheral tissues for heat production in endothermic animals. Maekawa et al (2013) described a significantly relationship between erythropoiesis, heamatological parameters and low temperature in mice.…”
Section: Introductionmentioning
confidence: 91%